Consultation on registration of new town or village greens : Proposed amendments to Schedule 1A (Exclusion of Right under section 15) to the Commons Act 2006Summary of responses and Government response.: Proposed amendments to Schedule 1A (Exclusion of Right under section 15) to the Commons Act 2006Summary of responses and Government response. (December 2013) - Great Britain., Department for Communities; Local Government,
No abstract available